CD14-mediated signal pathway of Porphyromonas gingivalis lipopolysaccharide in human gingival fibroblasts. - Watanabe, A (1996)
Lipopolysaccharide (LPS) induces expression of inflammatory cytokines in monocytes/macrophages via CD14, one of the LPS receptors, which is expressed predominantly in these cells. It has been demonstrated that Porphyromonas gingivalis LPS (P-LPS) also is able to induce inflammatory cytokines in human gingival fibroblasts. Therefore, it is important to determine whether CD14 is expressed in gingival fibroblasts and to define the P-LPS-mediated signal-transducing mechanism in the cells. In this study, we observed unexpectedly by immunohistochemical, Western blotting (immunoblotting), and Northern (RNA) blotting assays that CD14 is expressed at high density in human gingival fibroblasts. P-LPS-induced expression of the monocyte chemoattractant protein 1 (MCP-1) gene in the cells was inhibited markedly by treatment with anti-human CD14 antibody and was completely inhibited by herbimycin A, a potent inhibitor of tyrosine kinase. The inhibitor also dramatically inhibited monocyte chemotactic activity of and MCP-1 production by the cells. Furthermore, P-LPS-induced expression of the MCP-1 gene in the cells also was blocked by inhibitors of two transcription factors, i.e., curcumin, an inhibitor of AP-1, and pyrolidine dithiocarbamate, an inhibitor of NF-kappaB. Both inhibitors inhibited monocyte chemotactic activity in the culture supernatant of P-LPS-treated cells. Gel shift mobility assay showed stimulation of the AP-1 and NF-kappaB contents in P-LPS-treated cells. This study is the first to demonstrate the expression of CD14 in human gingival fibroblasts and to show that the signal-transducing pathway of P-LPS in the cells is mediated by CD14.